The Impact of Periodized Sit-to-Stand Exercises on Enhancing Gross Motor Skills and Balance in Children with Down Syndrome - Prananta, Marietta Shanti; Sari, Dian Marta; Paramita, Ika Ayu; Trianasari, Nurvita; Wijaya, Laurentia Cindy Gani; Santoso, Patricia Helena Christiani (Faculty of Medicine, Universitas Airlangga, 2025)
Background: Down syndrome (DS) is a congenital disorder with multiple chromosomal disorders. That causes growth disorders and changes the structure of the brain, like physical growth retardation, inability to learn, and other ailments of the cardiovascular system, thyroid glands, and blood cancer. The brain diminishes in size and maturation problems, and pathophysiological processes cause delayed motor development. Disorders often found in children with DS include hypotonia, ligamentous laxity, decreased muscle strength, postural control, proprioception, and cognitive disorders. Strengthening exercises in Down Syndrome children is thought to improve their motor and balance skills. The objective of this study was to assess the effect of periodic sit-to-stand strengthening exercises on Down Syndrome.Material and Methods: Children aged 7-12 years with Down Syndrome from Perhimpunan Orang Tua Anak Down Syndrome (POTADS) in Bandung participated in a seven-week sit-to-stand exercise intervention using a quasi-experimental design with a Pretest-Posttest Group approach (n=16). The initial load was 30% of body weight at 1 RM, progressively increasing to 70% by the seventh week, with adjustments based on re-measurements at week four. The intervention incorporated unloading and overloading phases and was performed thrice weekly at participants' homes. GMFM dimensions D and E and PBS were used to assess outcomes.Result: The result showed an increase in the D and E dimensions from the GMFM and PBS scores.Conclusion: Standing, walking, running, jumping motor, and balance skills in children with DS administered sit-to-stand exercise intervention with increased periodization.